FIGHTING FOR WOMEN EXISTENCE IN POPULAR ESPIONAGE MOVIES SALT (2010) AND ZERO DARK THIRTY (2012) - Benita Amalina (Universitas Gadjah Mada, 2016)
American spy movies have been considered one of the most profitable genre in Hollywood. These spy movies frequently create an assumption that this genre is exclusively masculine, as women have been made oblivious and restricted to either supporting roles or non-spy roles. In 2010 and 2012, portrayal of women in spy movies was finally changed after the release of Salt and Zero Dark Thirty, in which women became the leading spy protagonists. Through the post-nationalist American Studies perspective, this study discusses the importance of both movies in reinventing women’s identity representation in a masculine genre in response to the evolving American society. Keywords: American women, hegemony, representation, Hollywood, movies, popular culture